Seismocardiographic Signal Variability During Regular Breathing And Breath Holding At Different Airway Pressures - Sandler, Richard H.; Ahdy, Sherif; Hassan, Tanvir; Rahman, Badrun; Raval, Nirav; Mentz, Robert; Mansy, Hansen (Journal of cardiac failure, 2024)
Seismocardiography (SCG) refers to cardiac-induced chest wall vibrations. Preliminary investigations have suggested possible SCG utility for HF monitoring. Potentially limiting SCG clinical usefulness is the signal variability, which emerges from several potential sources including respiration effects and sensor location placement differences. Previous studies suggested that clustering normal breathing SCG beats during normal breathing using unsupervised machine learning could reduce the respiration related SCG variability. To increase understanding of the mechanism of respiration impact on SCG variability, the effects of breath holding and of intrathoracic pressure alterations were investigated in the current study. Compare SCG variability during normal breathing and breath holding at varying airway pressures. 21 healthy subjects (14 Females, 7 Males, 21±2y) were studied with simultaneous measurement of SCG (at the 4th ICS near the left lower sternal border), ECG and spirometry. Data was collected during normal breathing and breath holding. Breath holding was performed at end-inspiration and end-expiration with measured airway pressures of 0, ± 2-4 and ± 15-20 cm water. SCG beats were then segmented using the ECG-R waves. Normal breathing SCG beats were clustered into two groups with similar waveform morphologies using the “k-medoid” algorithm based on prior research. The intra-group variability was calculated and compared between normal breathing and breath holding. Figure 1 shows the intra-group variability (mean±std), demonstrating that clustering normal breathing SCG beats and SCG acquired during breath hold at zero airway pressure reduced the intra-group variability compared to the unclustered normal breathing SCG (p < 0.05). As the airway pressure during breath hold changed (both with increased and with decreased pressures) , the intra-group variability increased (p < 0.05). Mechanism for this finding for both increased and decreased pressures in unclear, but the magnitude of the change compared to the small intrathoracic pressure differences suggest that autonomic or other factors may be playing a role. Clustering normal breathing SCG beats or acquiring SCG during breath hold at zero airway pressure (open glottis) could reduce the respiration based SCG variability. Intrathoracic pressure is a source of SCG variability, and pressure maneuvers demonstrating SCG changes may prove to be useful features in future SCG HF diagnostic and monitoring studies.